Childhood Sexual Abuse and Depression among American Indians in Adulthood. Issue 2 (27th February 2019) - Easton, Scott D; Roh, Soonhee; Kong, Jooyoung; Lee, Yeon-Shim
Abstract: The present study investigated distal and proximal factors associated with depression among a sample of 479 American Indian (AI) adults in the Midwest. Distal factors included histories of childhood sexual abuse (CSA) and other childhood adversities. Proximal factors included levels of health self-efficacy and treatment for alcohol problems. The study also examined the moderating effect of treatment for alcohol problems on the relationship between CSA and depression. In model 1, results indicate that CSA was positively related to depression after controlling for demographic and background variables. In model 2, childhood adversities and treatment for alcohol problems were associated with increased depression in AI adults; CSA became nonsignificant. As a protective factor, level of health self-efficacy was negatively associated with depression. In model 3, treatment for alcohol problems magnified the effect of CSA on depression. These findings suggest that early traumatic experiences may have persistent, harmful effects on depression among AIs; one mechanism exacerbating the impact of CSA on depression is treatment for alcohol problems. Targeted interventions are needed to mitigate the long-term negative health effects of childhood trauma in this population and to strengthen proximal protective factors, such as health self-efficacy.